Intersubunit allosteric communication mediated by a conserved loop in the MCM helicase. - Barry, E; Lovett, J; Costa, A; Lea, S; Bell, S (2009)
The minichromosome maintenance (MCM) helicase is the presumptive replicative helicase in archaea and eukaryotes. The archaeal homomultimeric MCM has a two-tier structure. One tier contains the AAA+ motor domains of the proteins, and these are the minimal functional helicase domains. The second tier is formed by the N-terminal domains. These domains are not essential for MCM helicase activity but act to enhance the processivity of the helicase. We reveal that a conserved loop facilitates communication between processivity and motor tiers. Interestingly, this allostery seems to be mediated by interactions between, rather than within, individual protomers in the MCM ring.